Improvement Sistem Motor Ply Untuk Mengurangi Scrap Ply Melipat Pada Proses Cutting Produksi Ban - Falah, Muhammad Rafi Aimar; Wardoyo, Adik Susilo (Jurnal Instrumentasi dan Teknologi Informasi (JITI), 2024)
The Plant Passenger Car Radial (PCR) produces radial tires and has a Non-Reinforcing Materials Department with various divisions, including the Ply Bias cutting division. One common issue in the bias cutting process is folded ply scraps, mainly found at the end of the treatment roll. Analysis revealed that the problem resulted from the start-stop operation of the let-off motor, causing the treatment roll to twist and the plies to fold. To address this issue, modifications were made to the let-off motor. An inverter was added to adjust the motor speed according to the ply width, and the PLC program was modified to synchronize the motor speed with the HMI recipe. Through five successful trials, the motor speed was effectively adjusted for different ply sizes, reducing the residual rotation of the treatment roll. Data collected showed that prior to the modification, DBC-3 had 205 kg of folded ply scraps in March 2023. After the modification in May 2023, the folded ply scrap decreased to 138 kg, a reduction of 32.7% compared to March.